Efeitos da estimulação transcraniana por corrente contínua no desempenho de atletas de Taekwondo - Paulo Henrique Caldeira Mesquita (2019)
The transcranial direct current stimulation (tDCS) is a neuromodulatory technique used as an ergogenic aid in the sports context. After an integrative review of the literature was carried out, it was possible to verify that, despite some promising effects, it is not possible to ensure its effectiveness, mainly because of the considerable heterogeneity of the tDCS and testing protocols adopted. Furthermore, there are limited studies that investigated athletes performing complex tasks, specific to their sports events. Therefore, the aim of the present dissertation was to investigate the effects of tDCS on the performance and psychophysiological responses of taekwondo athletes. Two experiments were conducted. Experiment I: 12 (8M) international/national level athletes received a-tDCS or sham treatment over the primary motor cortex (M1) in a randomized and counterbalanced manner. The stimulation was delivered at 1.5 mA for 15 minutes, using an extracephalic bi-hemispheric montage. The athletes performed the Progressive Specific Taekwondo Test (PSTT) 10 minutes after the stimulation. The subjects’ heart rate (HR) was monitored continuously during the test and their rating of perceived exertion (RPE) were registered at the end of each stage and at test cessation. Experiment II: The experiment II followed the same design of the experiment I, and had a sample of 19 (12M) international/national level. The athletes performed countermovement jumps and the Frequency Speed of Kick Test multiple sets (FSKTmult) immediately (moment 1) and 60 minutes (moment 2) after the stimulation. The athletes should also report their session RPE at each moment. In experiment I, no significant changes were found for any of the variables of the PSTT (p>0.05) nor for the HR (p>0.05) and RPE (p>0.05) responses. In experiment II, the total number of kicks (FSKTtotal) was lower in the a-tDCS condition compared to the sham condition (p<0.01). Further, FSKTtotal was higher at moment 2 (p<0.05). Similarly, the session RPE was higher at the a-tDCS condition (p<0.05) and higher at moment 2 (p<0.05). There were no differences in the countermovement jump performance (p>0.05). The combined results of the present dissertation showed that the a-tDCS of the M1 using an extracephalic bi-hemispheric montage, did not alter the aerobic performance and worsened the anaerobic performance of the taekwondo athletes. The results suggest that the anodal tDCS of the M1 may not be beneficial for the performance of taekwondo athletes in specific tasks.